Proceedings of the 13th Annual ACM International Conference on Mobile Computing and Networking 2007
DOI: 10.1145/1287853.1287863
|View full text |Cite
|
Sign up to set email alerts
|

Reliable density estimates for coverage and connectivity in thin strips of finite length

Abstract: Deriving the critical density (which is equivalent to deriving the critical radius or power) to achieve coverage and/or connectivity for random deployments is a fundamental problem in the area of wireless networks. The probabilistic conditions normally derived, however, have limited appeal among practitioners because they are often asymptotic, i.e., they only make high probability guarantees in the limit of large system sizes. Such conditions are not very useful in practice since deployment regions are always … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
92
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
4
4
2

Relationship

1
9

Authors

Journals

citations
Cited by 139 publications
(95 citation statements)
references
References 34 publications
2
92
0
1
Order By: Relevance
“…In trap coverage, coverage holes are allowed to exist as long as the diameters of the holes are bounded. Sensor density estimation for these coverage requirements are derived [14], [4], [16], [5]. The optimal deterministic deployment pattern for 1-coverage is based on triangle lattices, which has been proved in [13].…”
Section: Related Workmentioning
confidence: 99%
“…In trap coverage, coverage holes are allowed to exist as long as the diameters of the holes are bounded. Sensor density estimation for these coverage requirements are derived [14], [4], [16], [5]. The optimal deterministic deployment pattern for 1-coverage is based on triangle lattices, which has been proved in [13].…”
Section: Related Workmentioning
confidence: 99%
“…In [4] the problem of local barrier coverage is introduced and it is shown that it is possible for individual sensors to locally determine the existence of local barrier coverage, even when the region of deployment is arbitrarily curved. Techniques for deriving density estimates for achieving barrier coverage and connectivity in thin strips are introduced in [1], where sensors are deployed as a barrier to detect moving objects and events. In all these instances the problem studied concerns static optimal sensor deployment patterns and there is no concept of mobility of the sensors.…”
Section: Related Workmentioning
confidence: 99%
“…It shows that it is possible for individual sensors to locally determine the existence of local barrier coverage, even when the region of deployment is arbitrarily curved. Techniques for deriving density estimates for achieving barrier coverage and connectivity in thin strips are studied in [1], where sensors are deployed as a barrier to detect moving objects. In all these instances the problem studied concerns static optimal sensor deployment patterns and there is no concept of movement of the sensors.…”
Section: Related Workmentioning
confidence: 99%